A quality-aware cloud management service for computational modellers. (1st January 2013) - Nizamani, Shahzad; Dew, Peter; Djemame, Karim
This research sets out to help computational modellers, to select the most cost effective cloud service provider. A novel quality-aware computational cloud management service (QAComPMS) is proposed and evaluated. This selects the best (cheapest) cloud provider's service and then automatically runs it. QaComPMS includes an integrated ontology that provides a standard specification and a common vocabulary for describing different cloud provider's services. This classification is then used by a MatchMaker to automatically select the highest ranked service that meets the user requirements. A SAWSDL interface is used to exchange information between the QAComPMS's internal services. QAComPS is the key internal service responsible for selection process. This service has been evaluated for accuracy and efficiency against quality matchmaking process (QMP) and analytical hierarchy process (AHP). The results for the evaluation were very promising and demonstrated its potential to make cloud computing more accessible and cost effective for computational modellers.